The development of a principal change leadership competency model: a structural equation modelling (SEM) approach - Kin, Tai Mei; Abdull Kareem, Omar; Nordin, Mohamad Sahari; Bing, Khuan Wai (Commonwealth Council for Educational Administration and Management (CCEAM), 2014)
The objectives of the study were twofold: to develop a substantiated Principal Change Leadership Competency Model (PCLCM) and to develop an instrument to identify change leadership competencies that facilitate change and maximise change effctiveness in secondary schools. A total of 936 teachers from 47 high-performing schools in Malaysia completed the survey. Structural equation modelling was applied to test the models. An exploratory factor analysis was employed to identify the underlying factors, while a confimatory factor analysis was applied to test the measurement models. The analysis yielded a four-factor PCLCM: a) goal framing; b) capacity building; c) defusing resistance and conflct; and d) institutionalising. The results demonstrated a good fi of the model: normed x2=3.184, TLI=.983, CFI=.987 and RMSEA=.048. The results also provided evidence for convergent validity, discriminant validity and construct reliability. The PCLCM is a coherent premier empirically tested model derived in a local Malaysian cultural education setting. It provides direction for practitioners as useful feedback in planning, designing, implementing and evaluating future training and development programmes for school principals. Specifially, it is an effctive training needs analysis tool tailored for school principals to identify their distinct needs on relevant training programmes at the diffrent stages of change. It therefore has far-reaching implications for the one-size-fis-all approach frequently employed by trainers and, thus, maximising learning impact. In addition, the Principal Change Leadership Competency Scale is a promising and welcome tool for both practitioners and relevant parties. With only 12 items, it covers four phases of change. It is economic, easy to administer and not time consuming.